2016
DOI: 10.4067/s0718-95162016005000017
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation with selenobacteria and arbuscular mycorrhizal fungi to enhance selenium content in lettuce plants and improve tolerance against drought stress

Abstract: This study evaluated the co-inoculation effect of the endophytic selenobacteria Bacillus sp., Klebsiella sp. or Acinetobacter sp. and the arbuscular mycorrhizal (AM) fungus Rhizophagus intraradices on lettuce plants grown under drought conditions. Plants inoculated with both microorganisms were able to enhance the Se content in their shoots (1 to 6 µg plant -1 ) and promote macro-and micronutrient uptake. Moreover, the inoculated plants showed significant tolerance to drought stress, as determined by their ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 43 publications
2
26
0
1
Order By: Relevance
“…The highest dry matter content was obtained with the inoculation of a mixture of both strains (AG-70 + AG-54) (Figure 1), which agrees with the results obtained in previous studies that have described that soil beneficial bacteria would promote plant growth under abiotic stress. In this sense, Durán et al (2016) found similar results in lettuce inoculated with PGPR strains (Bacillus sp. and Klebsiella sp.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The highest dry matter content was obtained with the inoculation of a mixture of both strains (AG-70 + AG-54) (Figure 1), which agrees with the results obtained in previous studies that have described that soil beneficial bacteria would promote plant growth under abiotic stress. In this sense, Durán et al (2016) found similar results in lettuce inoculated with PGPR strains (Bacillus sp. and Klebsiella sp.…”
Section: Discussionsupporting
confidence: 65%
“…This agrees with our results as the bacterial strains under study promoted positive effects on the root system by increasing the production capacity of auxin, and thus promoting an increase in root length (Figure 3); this indicate that the inoculation with these strains can be a morphological strategy to increase tolerance to water stress. Glick (2014) Regarding stomatal conductance (Table 1) produce an improved rate of photosynthesis and, consequently, increase leaf water potential, which plays an important role in the tolerance of plants to water stress (Durán et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in the same line with those of Rattan et al (2005) and Lone et al (2003). The prolonged application of treated and untreated wastewaters results in significant buildup of heavy metals in the soils (Khan et al, 2008;Ghosh et al, 2012;Durán et al, 2016) and grown vegetables and cereals which they subsequently transfer to the food chain causing potential health risk to consumers (Singh et al, 2010;Gupta et al, 2011). Heavy metals concentrations in plants grown on wastewater-irrigated soils were reported to be significantly higher than those grown on fresh water-irrigated soils (Khan et al, 2008;Singh et al, 2010;Gupta et al, 2011).…”
Section: Heavy Metals In the Roots And Shoots Of Lettuce And Spinach mentioning
confidence: 99%
“…Until now, mycorrhiza associations have been studied intensively for decades by its role to tolerate biotic and abiotic stress, plant productivity, nutrients acquisition and plant productivity ( Van der Heijden et al, 2015). Specifically, a recent study performed by Durán et al (2016) …”
Section: Discussionmentioning
confidence: 99%